DOLZARB ISSUES OF SOCIAL AND HUMANITARIAN SCIENCES (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
Today, the problem of teaching social humanities, critical thinking, and the extent to which social sciences are taught is the most responsible and urgent issue for the society.